A Characterization of Actuation Techniques for Generating Movement in Shape-Changing Interfaces. Issue 5 (4th May 2017) - Taher, Faisal; Vidler, John; Alexander, Jason
ABSTRACT: This article characterizes actuation techniques for generating movement in shape-changing displays with physically reconfigurable geometry. To date, few works in human–computer interaction literature provide detailed and reflective descriptions of the implementation techniques used in shape-changing displays. This hinders the rapid development of novel interactions as researchers must initially spend time understanding technologies before prototyping new interactions and applications. To bridge this knowledge gap, the authors propose a taxonomy that classifies actuator characteristics and simplifies the process for designers to select appropriate technologies that match their requirements for developing shape displays. They scope the investigation to linear actuators that are used in grid configurations. The taxonomy is validated by (a) examining current implementation techniques of motorized, pneumatic, hydraulic, magnetic, and shape-memory actuators in the literature, (b) constructing prototypes to address limited technical details and explore actuator capabilities in depth, (c) describing a use-case scenario through a case study that details the construction of a 10 × 10 actuator shape-display, and (d) a set of guidelines to aid researchers in selecting actuation techniques for shape-changing applications. The significance of their taxonomy is twofold. First, the authors provide an original contribution that enables HCI researchers to appropriately select actuation techniques and build shape-changing applications. This is situated amongst other past works that have investigated broader application scenarios such as a shape-changing vocabulary, a framework for shape transformations, material properties, and technical characteristics of various actuators. Second, they carry out in-depth investigations to validate their taxonomy and expand the knowledge of vertical actuation in shape-changing applications to enable rapid development.